SISTEM PENGALIHAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) MENJADI PAJAK DAERAH DI KABUPATEN TULUNGAGUNG - VERSI SETYAWATI, RAHAYUNING Versi (Jurnal Akuntansi AKUNESA, 2013)
This research was conducted to find out the system redirects the Bea acquisition of rights tothe Land and buildings became local taxof Tulungagung Regency. This research usesqualitative descriptive method andthe file used in this research is the documentation. Objectsin this research is income, dept. financial management and local asset tulungagung district.This research result is the transfer of rights over the land and building smoothly enforced bylocal government tulungagung district. Income, dept. financial management and local assetable to socialize people associated payment socialization proper.Keywords : Bea acquisition of rights to the Land and buildings, local tax.